2007
DOI: 10.1262/jrd.18139
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the Porcine Uterine Endometrium During the Estrous Cycle, Early Pregnancy and Post Partum

Abstract: Abstract. The mammalian uterus changes dramatically during the estrous cycle, pregnancy, and involution post partum. Dynamic changes in the uterine endometrium are a type of homeostasis and proceed with proliferation and exclusion of cells. Homeostasis of the uterus is closely related to apoptosis involving various hormones and cyctokines. The objective of the present study was to determine the morphological features and occurrence of apoptosis in the porcine endometrium during the estrous cycle, early pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…In pigs, a non‐menstruating species, there is repeated endometrial hyperplasia but, in the absence of implantation, apoptosis is observed. Interestingly, the peak of apoptotic cell death in stromal cells occurs on Days 4–8 (Okano et al, ) and in the glandular and luminal epithelium on Day 15 and Days 17–19, respectively, of the pig estrous cycle (Wasowska et al, ). Xu et al () further described increased side‐population cell proliferation after stimulation with 17β‐estradiol, which was inhibited by the estrogen receptor antagonist ICI182780, indicating to these authors that estrogen can directly stimulate side‐population cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, a non‐menstruating species, there is repeated endometrial hyperplasia but, in the absence of implantation, apoptosis is observed. Interestingly, the peak of apoptotic cell death in stromal cells occurs on Days 4–8 (Okano et al, ) and in the glandular and luminal epithelium on Day 15 and Days 17–19, respectively, of the pig estrous cycle (Wasowska et al, ). Xu et al () further described increased side‐population cell proliferation after stimulation with 17β‐estradiol, which was inhibited by the estrogen receptor antagonist ICI182780, indicating to these authors that estrogen can directly stimulate side‐population cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the basic events of uterine cellular change is physiological cell turnover, which involves cell death by apoptosis and cell renewal by proliferation (Spencer et al 1996;Toki et al 1998). Previous studies in several mammalian species have demonstrated an inverse correlation between cell apoptosis and cell proliferation in the uterus (Kokawa et al 1996;Sato et al 1997;Tao et al 1998;Pampfer and Donnay 1999;Dharma et al 2000;Vaskivuo et al 2000;Chu et al 2002Chu et al , 2006Joswig et al 2003;Van Cruchten et al 2003;Harada et al 2004;Wei et al 2005;Narkar et al 2006;Zhang and Paria 2006;Okano et al 2007; Roberto da Costa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that apoptosis plays an important role in human trophoblastic villi differentiation and syncytium formation (Huppertz, Kadyrov, & Kingdom, ). In sows, at the beginning of gestation, apoptosis has been related to placental villi homoeostasis through cell remodelling (Cristofolini et al, ; Merkis, Cristofolini, Sanchis, & Koncurat, ; Okano, Ogawa, Takahashi, & Geshi, ) while at the end of human and swine pregnancy, cell remodelling by apoptosis would be contributing to foetal and maternal membranes separation (Barrio et al, ; Cristofolini et al, ). The first findings of placental cell remodelling by apoptosis in at term caprine placenta were described by our research group (Cristofolini, Turiello, Sanchis, Cufre, & Merkis, ).…”
Section: Introductionmentioning
confidence: 99%